Design and comprehensive testing a 2.4 GHz antenna for WiFi access point - Firdaus Firdaus; Afida Nurul Fatimah; Yulindon Yulindon; Ratna Dewi (Universitas Ahmad Dahlan, 2020)
A small size patch antenna for replacing TP-LINK WA 701 ND access point (AP) internal antena for 2.4 GHz is proposed. Measurements are carried out on AP external antenna to get the basic parameter of the antenna i.e. return loss, bandwidth, radiation pattern, and polarization. The patch antenna is designed by using IE3D simulator on FR4 material with the thickness of 1.6 mm and the dielectric constant of 4.4. The 42×28×1.6 mm overall size of the designed antenna is printed on FR 4 substrate, measured and compared to external AP antenna. The measurement result shows good agreement between simulation and designed antenna. The printed antenna covers 2.4 GHz, the gain of 2.5 dBi, and has linier polarization. This antenna is much smaller than 190×15×15 mm conventional TP-LINK WA 701 ND AP antennas and allows it to be hidden and integrated on the AP printed circuit board. The comparation of the designed antenna and external AP antenna is also conducted by evaluating both antenna performance on TP-LINK WA 701 ND AP by accessing it on a laptop on different access distance.